Adiponectin deficiency is a critical factor contributing to cognitive dysfunction in obese mice after sevoflurane exposure - Chu, John Man Tak; Chiu, Suki Pak Wing; Wang, Jiaqi; Chang, Raymond Chuen Chung; Wong, Gordon Tin Chun (Molecular medicine (Cambridge, Mass.), 2024)
The number of major operations performed in obese patients is expected to increase given the growing prevalence of obesity. Obesity is a risk factor for a range of postoperative complications including perioperative neurocognitive disorders. However, the mechanisms underlying this vulnerability are not well defined. We hypothesize that obese subjects are more vulnerable to general anaesthesia induced neurotoxicity due to reduced levels of adiponectin. This hypothesis was tested using a murine surgical model in obese and adiponectin knockout mice exposed to the volatile anaesthetic agent sevoflurane. Obese mice were bred by subjecting C57BL/6 mice to a high fat diet. Cognitive function, neuroinflammatory responses and neuronal degeneration were assessed in both obese and lean mice following exposure to 2 h of sevoflurane to confirm sevoflurane-induced neurotoxicity. Thereafter, to confirm the role of adiponectin deficiency in, adiponectin knockout mice were established and exposed to the sevoflurane. Finally, the neuroprotective effects of adiponectin receptor agonist (AdipoRon) were examined. Sevoflurane triggered significant cognitive dysfunction, neuroinflammatory responses and neuronal degeneration in the obese mice while no significant impact was observed in the lean mice. Similar cognitive dysfunction and neuronal degeneration were also observed in the adiponectin knockout mice after sevoflurane exposure. Administration of AdipoRon partially prevented the deleterious effects of sevoflurane in both obese and adiponectin knockout mice. Our findings demonstrate that obese mice are more susceptible to sevoflurane-induced neurotoxicity and cognitive impairment in which adiponectin deficiency is one of the underlying mechanisms. Treatment with adiponectin receptor agonist ameliorates this vulnerability. These findings may have therapeutic implications in reducing the incidence of anaesthesia related neurotoxicity in obese subjects.